(untitled) (Fiep Bulletin - online, 2011)
The relationship between leisure and swimming are highlighted in many studies, which have come up with great results. The play is transforming the practice of swimming for children, making it much more pleasant and provide excellent benefits. The playful nature makes it easy to adapt to the new environment, showing that "ludica" appears as an icon in the renewal in the teaching didactic teaching in the wonderful world of water. Using the method of literature review, we sought the following objective: to determine whether the playfulness helps in learning to swim as a motivating factor. The playfulness is present in day-to-day, in homes, streets and parks, being able to capture the attention of your target audience. Accordingly, it is nonetheless entertaining feature when you do not see the time passing, or even when one realizes that the class went in an instant, making learning more enjoyable and productive. Motivation provides satisfaction and a renewed interest in what he is doing. The motivated student is involved in the matter and finds himself increasingly interested. One must know how the student is understanding, and help him overcome his difficulties. It is established, so the difference of swimming and swimming traditional formal, causing the student to develop better and more joyful activity proposed by the teacher and thus tends to an end more successfully. We conclude that the play element is of great importance in swimming lessons, but is not highly valued in the teaching pedagogy. With this playful look at the dynamics reaffirms role in physical education, learning and life.